2015
DOI: 10.1002/ppul.23169
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnography for the diagnosis of sleep disordered breathing in children under 2 years of age

Abstract: Summary. Objectives: To describe clinical polysomnography (PSG) results, sleep physicians' diagnosis, and treatment of sleep disorder breathing in children less than 2 years of age. Study Design: Retrospective clinical chart review at a pediatric tertiary care center, pediatric sleep laboratory. Subject Selection: Children less than 2 years of age who underwent clinical PSG over a 3-year period. Methodology: PSG results and physician interpretations were identified for inclusions. Children were excluded if eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…Healthy full‐term neonates have higher frequency of apneas and hypopneas than older children (mean neonatal apnea‐hypopnea index, AHI, was reported to be 14.9 ± 9.1 among 30 healthy infants, with neonatal obstructive AHI 2.3 ± 2.5, while obstructive AHI > 1 is considered abnormal for children > 12 months of age) . Despite clinical observations of sleep‐disordered breathing (SDB) patterns on polysomnography, parameters to guide clinically appropriate diagnostic limits for SDB are not currently well‐defined for neonates or infants < 1 year …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy full‐term neonates have higher frequency of apneas and hypopneas than older children (mean neonatal apnea‐hypopnea index, AHI, was reported to be 14.9 ± 9.1 among 30 healthy infants, with neonatal obstructive AHI 2.3 ± 2.5, while obstructive AHI > 1 is considered abnormal for children > 12 months of age) . Despite clinical observations of sleep‐disordered breathing (SDB) patterns on polysomnography, parameters to guide clinically appropriate diagnostic limits for SDB are not currently well‐defined for neonates or infants < 1 year …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Despite clinical observations of sleep-disordered breathing (SDB) patterns on polysomnography, parameters to guide clinically appropriate diagnostic limits for SDB are not currently welldefined for neonates or infants < 1 year. 5 Infants who are born prematurely are predisposed to adverse cognitive outcomes 6 and appear to be at risk for later SDB. 7 Habitual snoring with associated arousals, even in the absence of measurable sleep apnea, among infants is associated with suboptimal motor developmental scores.…”
mentioning
confidence: 99%
“…Information on the criteria to be used to determine SDB in infants remains largely nonexistent. In a retrospective study on 233 infants <2 years, De Haan et al identified infants <6 months as a distinct group with significant differences in PSG sleep and respiratory indices compared to older groups. Compared to SDB classification by experienced sleep physicians, the pediatric apnea‐hypopnea index (AHI) overestimated SDB severity in infants <6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Without this information, however, Experienced clinicians will use alternative clinical criteria to define severity . This is based on clinical experience, which makes it imprecise—different clinicians will weight various clinical parameters differently.…”
Section: Introductionmentioning
confidence: 99%
“…Children under 2 years of age have specific anatomical and physiologic factors that make them uniquely at risk for SDB. 3 In the article, in this issue, by Dr. DeHaan et al, 4 three experienced sleep physicians evaluated a group of children in this age group, referred for evaluation of suspected SDB. These children also underwent standard polysomnography (PSG).…”
Section: Introductionmentioning
confidence: 99%